Quantitative Collateral Assessment on CTP in the Prediction of Stroke Etiology - Shi, F.; Zeng, Q.; Gong, X.; Zhong, W.; Chen, Z.; Yan, S.; Lou, M. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Patients with stroke etiology of large-artery atherosclerosis were thought to have better collateral circulation compared with patients with other stroke etiologies. We aimed to investigate the association between stroke etiology and collateral circulation with a new quantitative collateral assessment method.MATERIALS AND METHODS: This retrospective study reviewed data from consecutive patients with proximal anterior artery occlusion who underwent CTP before reperfusion therapy. CBF maps were derived from CTP. A new indicator, maximum CBF of collateral vessels within the Sylvian fissure (cCBFmax), was applied to quantitatively assess the collateral status. The relationship between collateral status and stroke etiology was investigated.RESULTS: A total of 296 patients were finally analyzed. The median cCBFmax was significantly higher in patients with large-artery atherosclerosis than in those without it (92 [interquartile range, 65–123] mL/100 g/min versus 62 [interquartile range, 46–82] mL/100 g/min; P < .001). Multivariable analysis revealed that a higher cCBFmax score was independently associated with large-artery atherosclerosis etiology (OR, 1.010; 95% CI, 1.002–1.018; P = .017) after adjustment. The area under the curve, sensitivity, and specificity of the final model in predicting the etiology of large-artery atherosclerosis were 0.870, 89.7%, and 75.2%, respectively.CONCLUSIONS: Patients with large-artery atherosclerosis had a more adequate collateral perfusion supply with the new quantitative collateral assessment. The new quantitative collateral measurement might contribute to the prediction of stroke etiology in the acute clinical scenario for patients with acute ischemic stroke.AISacute ischemic strokeAUCarea under the curvecCBFmaxmaximum CBF of collateral vessels within the Sylvian fissureCEcardioembolismIQRinterquartile rangeLAAlarge-artery atherosclerosisROCreceiver operating characteristic